Girls and violence: tracing the roots of criminal behavior - Ryder, Judith A. (Qualitative studies in crime and justice, 2014)
Girls and violence -- Understanding attachment gone wrong -- The first relationship: parental bonds -- Traumatic childhood experiences of loss -- Traumatic childhood experiences of violence -- Coping strategies: running, drugging, and self-harm -- Illegal acts: "I don't know if you consider that violence." -- Rethinking violence and delinquency